DESIGNING EDUCATION COMIC STRIPS AS SUPPLEMENTARY MATERIAL IN TEACHING MODAL VERBS OF OBLIGATION - Arismunandar, Vicky; Apriliaswati, Rahayu; Surmiyati, Surmiyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research is aimed at designing education comic strips as supplementary material in teaching modal verbs of obligation for "Bahasa Inggris Peminatan" to year-10 students of MAN 2 Pontianak. The method of this research was design and development research. The researcher applied ADDIE as the procedure. However, the researcher only implemented three phases, which were analyzing, designing, and developing (ADD) due to community activity restrictions enforcement. In the analyzing phase, the researcher interviewed the English teacher and observed the syllabus to get information about the students, and the teaching and learning situation. The results of the analysis found the cause of students' lack of understanding of the research subject. In the designing phase, the researcher observed the textbook and collected materials to design a significant product of education comic strips. The result is a concept map and prototype of the research product. In the developing phase, the researcher used "Comipo" to design the supplementary material for the students by combining the draft such as panels, characters, balloons, and effects. The final stage is a product that has been perfected, to then be validated. The researcher used expert validation to make sure the product is usable, with a score of 87%. In conclusion, it is found that education comic strips could assess the teaching of modal verbs of obligation